Mayo Clinic gastrointestinal imaging review - Johnson, Charles Daniel (Mayo Clinic scientific press (Series), 2014)
"Similar to the first edition, the goal of Mayo Clinic Gastrointestinal Imaging Review, 2nd Edition is to provide an atlas of common abnormalities that affect the gastrointestinal tract. This comprehensive review includes all imaging modalities used within GI radiology, as well as plain radiographs, fluoroscopy, ultrasound, CT, MR, angiography, and nuclear medicine. Focusing solely on adult conditions, the book is divided into 13 chapters covering a separate organ within the gastrointestinal system and a final exam chapter reviewing all chapter content. Each organ-focused chapter is subdivided into sections related to diseases or findings of that organ. Running headers allow the reader to rapidly identify the chapter and the section being viewed. Large, high-quality images are presented in a format so that they can be reviewed as unknowns. A discussion of the cases is presented as if it were a consultation-- with a description of the findings, differential diagnosis, and final diagnosis. A brief discussion of the disease is included. Emphasis is placed on brevity of the text and a single-page layout for all but a few cases. Study guides at the end of each section are in the form of tables summarizing major radiographic findings into differential considerations with brief imaging clues to a specific diagnosis and case references within the book. The end of each chapter lists differential diagnoses for the chapter's specific organ. Full-color composite anatomical illustrations show the immediately obvious appearance of common conditions that correlate with major radiologic findings"--Publisher's description